Pedagog wobec pluralizmu współczesnych teorii wychowania - Śliwerski, Bogusław (Horyzonty Wychowania, 2017)
The main problem undertaken by the author is presenting a pedagogue facing pluralism of contemporary theories of education. The author wonders what a teacher who is confronted with multitude of pedagogical theories should do, how to pull himself together in the world of chaos and disorder, where pedagogical approaches and orientations are competing witch one another, not eliminating anything at the beginning. The author refers to the metaphor of „hypermarket and labyrinth”. Both metaphors illustrate the world of pedagogy resembling a similar mass of theories, ideas and philosophies. It is the supermarkets that attempt to make the choice of diverse knowledge („goods”) available to society. Hypermarket becomes a peculiar kind of labyrinth, a territory where customers should skilfully get around. Therefore, a question arises: How can pedagogue entangled into the metaphor of hypermarket of theories of education avoid enslavement? The author thinks that he may simply not read, not study. He may adopt a critical attitude in the face of „catches” hidden in various theories. Finally, he may also look into his own pedagogical consciousness thoroughly, analyze his own rationality, think about knowledge he needs. The author thus states that pedagogues are faced with the task of reading, classifying and comparing a multitude of theories so that they can adopt those most valuable and so that they are able to make use of them in the process of education.